The Expansion of Qualitative Research Methods in Innovation Policy Studies - Eristian Wibisono (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2022)
AbstractThis paper intends to provide a general description of the position of a qualitative approach in the study of innovation policy and its possible expansion based on the experiences of experts from other disciplines. There is an important and urgent matter about improving young researchers' methodological skills in understanding complex innovation studies. By understanding and mastering various methodological skills, individual researchers, groups, or innovation study communities can provide comprehensive interpretations and insights from unit analysis to draw accurate conclusions in response to phenomena and planned research questions. Some of the research approaches suggested in this paper, namely ethnographic research and action research, require additional research skills in the field. The ethnographic approach and the participant approach allow young researchers to influence the research design by involving participants in the research in a planned manner. Therefore, it is appropriate to use a participatory approach as methodological enrichment in innovation studies. An ethnographic approach will benefit from the perspective of the innovation policy group. The qualitative approach described in this paper can be used in mixed methods, along with quantitative methods. Keywords: qualitative methods, mixed-methods, innovation, policy studies